Happy, Healthy and Productive Abroad: Exploring Sustainable Global Careers and Developing Future Research Directions - Zong, Shaofang; Suutari, Vesa; Mello, Rodrigo; Dickmann, Michael (Edward Elgar, 2026)
In response to growing global uncertainty, scholars and practitioners are increasingly becoming interested in the sustainability of careers. However, the novel and emerging sustainable careers concept has not yet been integrated into the international career field, where expatriates moving across cultures face unique challenges. This chapter builds on the sustainable career framework to analyze the career sustainability of expatriates in terms of their health, happiness, and productivity. It also highlights the key factors within the person, context, and time dimensions that influence expatriates’ career sustainability. By extending the sustainable career concept into the global career context, this chapter extends our understanding of the specific nature of career sustainability in the global career context and provides suggestions for future research.
Keywords: Career; Sustainable Career; Sustainable Global Career; Global Careers; International Careers; Expatriate; fi=Henkilöstöjohtaminen|en=Human Resource Management|